A sketch of 'family' as a field: From realized category to space of struggle. (August 2014) - Atkinson, Will
This article sets out the argument that 'family' relations constitute so many small-scale 'fields' in Pierre Bourdieu's sense. It does so primarily to put on firmer conceptual ground a valuable means of making sense of how broader structures of social and cultural domination are lived, reproduced and transformed in everyday life, though in so doing it also intends to challenge those who believe Bourdieu has little to offer scholars of familial life. Using Bourdieu's own brief reflections as a point of departure, it proceeds by putting substantive flesh on the foundational notion that 'family' constitutes a contested yet 'realized' category of thought before then sketching the constituent elements of family fields, namely internal doxa, struggles over capital, the existence of boundaries and embeddeness in broader 'universes' of family fields.